Effectiveness Of Using The Self-Registration Platform Machines (Apm) At Wava Husada Kepanjen Hospital - Fita Rusdian Ikawati; Farma Duana; Silfina Choirun Nisa (Journal of International Multidisciplinary Research, 2024)
The self-registration machine helps patients register them selves. The use of APM machines at Wava Husada Hospital has not been carried out properly for several reasons, such as Man, Method and Machine. The aim of this research is to evaluate the performance of APM users to identify the components and effects to increase the effectiveness of APM. Qualitative research methodologies were used in this study. Data was obtained from APM officers and medical records officers. The results of the research show that the presence of APM officers has helped the patient registration process, but there are several things that make the use of APM less effective at Wava Husada Hospital, namely in terms of staff, the lack of APM officers, in terms of the method of using APM is not carried out in accordance with the SOP, in terms of Machine errors or loading often occur. Consequently, there are too many patients, the registration process is thrown off, services are provided non-procedurally, and registration is completed by hand. Efforts made by officers to ensure that the use of APM runs well are adding APM officers, training APM officers on APM use, and improving internet quality so it doesn't load frequently.